THE EFFECTIVE METHODS OF MOTIVATING LANGUAGE STUDENTS. SUGGESTOPEDIA IS A METHOD AS A VEHICLE TO GET EFL STUDENTS INVOLVED THE LESSON - Rakhmonova Shakhnoza (Galaxy International Interdisciplinary Research Journal, 2022)
In English there is a well-known proverb -“You can lead a horse to water, but you can’t make him drink.” Motivating language learners looks like that. It includes not only leading them to English learning, but also making them thirsty for understanding of English of the target language. As a language learning, English learning has its own features that demand the learners to remember more, have practice more and interact more than other subjects. Students’ motivation is crucial for English learning. Therefore, English teachers must be organizers or leaders in teaching. They have an incredible responsibility to increase their students’ willingness to perform actively on English learning. The matter of motivation for educational career is an crucial issue since education programs and training styles can make a distinction to students’ academic achievement. There is, in fact, an increasing requirement to finding new disagreements to make contact with the advanced modifications of contemporary world. Teachers can have impact on students’ attributions in different ways.